Electromagnetic wave shielding material

The use of iron and nickel nanowires with a specific mass ratio and a dielectric in the electromagnetic shielding material addresses the limitations of existing materials by providing excellent high-frequency electromagnetic wave absorption and shielding performance.

JP2025038239AInactive Publication Date: 2025-03-18UNITIKA LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024230376
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2024-12-26
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing electromagnetic shielding materials are inadequate for high-frequency ranges, particularly in the quasi-mmillimeter and millimeter wave ranges, due to limited frequency band absorption and insufficient shielding performance.

Method used

A material comprising nanowires made of iron and nickel, with a mass ratio of 20/80 to 65/35, combined with a dielectric, which provides excellent electromagnetic wave shielding and absorption properties in the high frequency range.

Benefits of technology

The material achieves significant electromagnetic wave absorption and shielding, particularly in the 18-110 GHz frequency range, making it suitable for fifth-generation mobile communication systems and advanced driver assistance systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038239000013
    Figure 2025038239000013
  • Figure 2025038239000014
    Figure 2025038239000014
  • Figure 2025038239000015
    Figure 2025038239000015
Patent Text Reader

Abstract

To provide an electromagnetic wave shielding material that has excellent electromagnetic wave shielding properties, particularly excellent electromagnetic wave absorption properties, in the high frequency range of several tens of GHz (particularly quasi-millimeter waves and millimeter waves).SOLUTION: The present invention relates to an electromagnetic wave shielding material including nanowires composed of iron and nickel. The electromagnetic wave shielding material has a mass ratio (iron / nickel) of iron to nickel in the nanowires of 20 / 80 to 65 / 35. The electromagnetic wave shielding material further includes a dielectric. The dielectric is a binder. The ratio of the nanowires to the total of the nanowires and the dielectric is 10 mass% or more and less than 65 mass%. The ratio of the nanowires to the total of the nanowires and the dielectric is 40 mass% or more and 60 mass% or less. The volume resistivity is 10-2 Ωcm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electromagnetic wave shielding material having excellent electromagnetic wave shielding properties, particularly excellent electromagnetic wave absorption properties, in the high frequency range of several tens of GHz. [Background technology]

[0002] In recent years, the use of radio waves in the quasi-millimeter and millimeter wave ranges has been rapidly increasing in fifth-generation mobile communication systems and advanced driver assistance systems. Fifth-generation mobile communication systems use radio waves with frequencies such as n257 (26.50-29.50 GHz), n258 (24.25-27.50 GHz), n259 (39.5-43.50 GHz), n260 (37.00-40.00 GHz), and n261 (27.50-28.35 GHz) for wireless communication. Millimeter-wave radar, which is part of the advanced driver assistance system, senses the surroundings of the vehicle using radio wave beams with frequencies of 24.05-24.25 GHz for 24 GHz narrowband radar systems, 24.25-29.0 GHz for 24 GHz / 26 GHz UWB radar systems, 60.0-61.0 GHz for 60 GHz millimeter-wave radar systems, 76.0-77.0 GHz for 76 GHz millimeter-wave radar systems, and 77.0-81.0 GHz for 79 GHz high-resolution radar systems. These fifth-generation mobile communication systems and electronic components of millimeter-wave radars in advanced driver assistance systems differ from conventional ones in that they suppress the generation and effects of noise, including radio waves in the quasi-millimeter and millimeter-wave ranges, and there is a strong demand for suitable electromagnetic wave shielding materials.

[0003] Traditionally, the mainstream method for electromagnetic compatibility (EMC) of electronic devices has been to cover the device itself with a conductor such as a metal case. However, with the use of quasi-millimeter and millimeter waves in fifth-generation mobile communication systems and advanced driver assistance systems, as well as the miniaturization and high integration of electronic components, a phenomenon called auto-poisoning (intra-EMC) has become a problem, in which noise generated inside devices reduces the characteristics of electronic components such as semiconductors. To prevent auto-poisoning, materials that absorb radio waves are desired, rather than conventional conductors.

[0004] Metamaterial radio wave absorbers are known as electromagnetic wave shielding materials (radio wave absorbers) that absorb quasi-millimeter waves and millimeter waves, but the frequency band that they can absorb is very narrow, less than 0.1 GHz, and they are unsuitable for systems that perform large-capacity wireless communication using a wide band, such as fifth-generation mobile communication systems and millimeter-wave radars in advanced driving assistance systems. In addition, cited reference 1 discloses an electromagnetic wave shielding material that uses nickel nanowires. However, the electromagnetic wave shielding material in cited reference 1 has insufficient shielding performance, and there are problems with absorbing radio waves in particular. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-165996 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides an electromagnetic wave shielding material that has excellent electromagnetic wave shielding properties, particularly excellent electromagnetic wave absorption properties, in the high frequency range of several tens of GHz (particularly, the quasi-millimeter wave range and millimeter wave range). [Means for solving the problem]

[0007] The present inventors discovered that a material containing nanowires composed of iron and nickel can achieve the above object, and arrived at the present invention.

[0008] That is, the gist of the present invention is as follows. (1) An electromagnetic wave shielding material containing nanowires composed of iron and nickel. (2) The electromagnetic shielding material according to (1), wherein the mass ratio of iron to nickel (iron / nickel) in the nanowires is 20 / 80 to 65 / 35. (3) The electromagnetic wave shielding material according to (1) or (2), further comprising a dielectric. (4) The electromagnetic wave shielding material according to (3), wherein the dielectric is a binder. (5) The electromagnetic shielding material according to (3) or (4), wherein the ratio of the nanowires to the total of the nanowires and the dielectric material is 10% by mass or more and less than 65% by mass. (6) The electromagnetic shielding material according to (3) or (4), wherein the ratio of the nanowires to the total of the nanowires and the dielectric material is 40% by mass or more and 60% by mass or less. (7) Volume resistivity is 10 -2 The electromagnetic wave shielding material according to any one of (1) to (6), having a resistivity of Ω·cm or more. (8) A dispersion liquid containing the electromagnetic wave shielding material according to any one of (1) to (7). (9) A sheet comprising the electromagnetic wave shielding material according to any one of (1) to (7). (10) A film comprising the electromagnetic wave shielding material according to any one of (1) to (7). (11) An electronic component comprising the electromagnetic wave shielding material according to any one of (1) to (7). Effect of the Invention

[0009] According to the present invention, it is possible to provide an electromagnetic wave shielding material that has excellent electromagnetic wave shielding properties, particularly excellent electromagnetic wave absorption properties, in the high frequency range of several tens of GHz (particularly in the quasi-millimeter wave range and millimeter wave range). The electromagnetic wave shielding material of the present invention can be suitably used in electronic components of fifth generation mobile communication systems, advanced driving assistance systems, and the like. [Brief description of the drawings]

[0010] [Figure 1] 1 is a diagram showing the electromagnetic wave absorption properties in K band of Example 1. [Diagram 2] 1 is a diagram showing the electromagnetic wave absorption properties in Ka band of Example 1. [Diagram 3] 1 is a diagram showing the electromagnetic wave absorption properties in U band of Example 1. [Figure 4] 1 is a diagram showing the electromagnetic wave absorption properties in E band of Example 1. [Diagram 5] 1 is a diagram showing the electromagnetic wave shielding properties in K band of Example 1. [Figure 6] 1 is a diagram showing the electromagnetic shielding properties in Ka band of Example 1. [Figure 7] 1 is a diagram showing the electromagnetic wave shielding properties in U band of Example 1. [Figure 8] 1 is a diagram showing the electromagnetic wave shielding properties in E band of Example 1. [Figure 9] 13 is a diagram showing the electromagnetic wave absorption properties in K band of Example 5. [Figure 10] 13 is a diagram showing the electromagnetic wave absorption properties in Ka band of Example 5. [Figure 11] 13 is a diagram showing the electromagnetic wave absorption properties in U band of Example 5. [Figure 12] 1 is a diagram showing the electromagnetic wave absorption properties in E band of Example 5. [Figure 13] 13 is a diagram showing the electromagnetic wave shielding properties in K band of Example 5. [Figure 14] 13 is a diagram showing the electromagnetic shielding properties in Ka band of Example 5. [Figure 15] 13 is a diagram showing the electromagnetic wave shielding properties in U band of Example 5. [Figure 16] 13 is a diagram showing the electromagnetic wave shielding properties in E band of Example 5. [Figure 17] 1 is a diagram showing the electromagnetic wave absorption properties in K band of Comparative Example 2. [Figure 18] 1 is a diagram showing the electromagnetic wave absorption properties in Ka band of Comparative Example 2. [Figure 19] 1 is a diagram showing the electromagnetic wave absorbency in U band of Comparative Example 2. [Figure 20] 1 is a diagram showing the electromagnetic wave absorbency in E band of Comparative Example 2. [Figure 21] 13 is a diagram showing the electromagnetic shielding properties in K band of Comparative Example 2. [Figure 22] 13 is a diagram showing the electromagnetic shielding properties in Ka band of Comparative Example 2. [Diagram 23] 13 is a diagram showing the electromagnetic shielding properties in U band of Comparative Example 2. [Figure 24] 13 is a diagram showing the electromagnetic shielding properties in E band of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The electromagnetic wave shielding material of the present invention includes nanowires composed of iron and nickel.

[0012] In the present invention, the electromagnetic wave shielding (shielding) property is a property that takes into consideration both the performance of reflecting electromagnetic waves (electromagnetic wave reflectivity) and the performance of absorbing electromagnetic waves (electromagnetic wave absorption). The electromagnetic wave reflectivity means the performance of reflecting electromagnetic waves in the direction of the electromagnetic wave incident surface to suppress the transmission of electromagnetic waves to the opposite surface. The electromagnetic wave absorption property means the performance of converting the energy of electromagnetic waves into magnetism and heat to suppress the transmission of electromagnetic waves to the opposite surface. The electromagnetic wave shielding property and the electromagnetic wave absorption property can be measured by a free space method. In this specification, the high frequency band of several tens of GHz means a frequency range of 18 to 110 GHz (particularly 24.05 to 81.0 GHz). The quasi-millimeter wave means a frequency band of 20 to 30 GHz. The millimeter wave means a frequency band of 30 to 300 GHz.

[0013] The nanowires used in the present invention are fibrous materials having an average diameter of less than 1 μm. From the viewpoint of ease of production of the electromagnetic wave shielding material and further improvement of the electromagnetic wave shielding properties, particularly the electromagnetic wave absorbing properties, the nanowires preferably have an average diameter of 50 to 900 nm and an average length of 5 μm or more (particularly 10 μm or more), and more preferably have an average diameter of 70 to 700 nm and an average length of 15 to 500 μm. The aspect ratio of the nanowires used in the present invention is usually 10 or more (particularly 50 or more), and from the viewpoint of further improvement of the electromagnetic wave shielding properties (particularly the electromagnetic wave absorbing properties), it is preferably 10 to 1000, more preferably 50 to 500.

[0014] In this specification, the aspect ratio of the nanowires was calculated by calculating the long axis (length) / short axis (diameter) value of each nanowire from images taken with a SEM (scanning electron microscope), and the average value of 100 values ​​was used.

[0015] The morphology of iron and nickel constituting the nanowire is not particularly limited, but examples thereof include a structure in which iron and nickel are randomly arranged, a core-sheath structure in which nickel is arranged around iron, a core-sheath structure in which iron is arranged around nickel, and a particle chain structure of iron particles and nickel particles. Among these, a structure in which iron and nickel are randomly arranged is preferred from the viewpoint of improving electromagnetic wave shielding properties, particularly electromagnetic wave absorption properties.

[0016] The mass ratio of iron to nickel (iron / nickel) in the nanowire is not particularly limited. Magnetic materials are advantageous for absorbing electromagnetic waves, so the mass ratio of iron to nickel is preferably 20 / 80 to 65 / 35, more preferably 20 / 80 to 50 / 50, even more preferably 20 / 80 to 40 / 60, and particularly preferably 20 / 80 to 30 / 70. The mass ratio of Permalloy A (iron:nickel=21.5:78.5 (mass ratio)) is the most preferable because it further increases the magnetic permeability.

[0017] The method for producing the nanowires used in the present invention is not particularly limited, but may be, for example, a method in which an iron salt and a nickel salt are reduced in a reaction solution to produce a nanowire dispersion liquid, and then the nanowires are collected.

[0018] Examples of methods for producing a nanowire dispersion by reducing iron salt and nickel salt in a reaction solution include an electrolysis method using a positron oxide film and a liquid-phase reduction method. The liquid-phase reduction method is a method for reducing iron salt and nickel salt in a reaction solution while applying a magnetic field to obtain a dispersion. Among these, the latter method is preferred because it can be produced relatively inexpensively.

[0019] The iron salt and the nickel salt are preferably chlorides or acetates, and more preferably chlorides from the viewpoint of dispersibility of the resulting dispersion. Specifically, the iron salt is preferably iron(II) chloride or iron(II) chloride tetrahydrate, and the nickel salt is preferably nickel chloride or nickel chloride hexahydrate.

[0020] The total concentration of the iron salt and nickel salt in the reaction solution is preferably 10 to 1000 μmol / g, and from the viewpoints of controlling the shape of the resulting nanowires and improving the yield, is more preferably 10 to 500 μmol / g, and even more preferably 15 to 85 μmol / g.

[0021] From the viewpoints of controlling the shape of the resulting nanowires and improving the yield, it is preferable to add a citrate to the reaction solution. The amount of the citrate added is preferably 0.5 to 5 mol %, more preferably 0.5 to 3 mol %, based on the total amount of the iron salt and nickel salt.

[0022] The reaction solvent used in the reaction solution is preferably a highly polar reaction solvent, such as water, alcohol, glycol, etc. Ethylene glycol, which has a high boiling point and viscosity, is preferred because it is stable to the temperature of the reduction reaction and against the generated gas.

[0023] In the present invention, the property of the solution in the reduction reaction is important, and the reduction reaction does not proceed in the acidic to neutral region, and nanowires are not generated. Therefore, the property of the solution in the reduction reaction needs to be alkaline. The property of the solution may be adjusted by adding an alkaline compound, specifically, by adding an alkaline compound such as sodium hydroxide or potassium hydroxide. The amount of the alkaline compound added is preferably 1 mol or less per mol of the total of the iron salt and the nickel salt, and is preferably 0.2 to 1 mol, more preferably 0.5 to 0.8 mol, from the viewpoint of the reduction reactivity of the iron salt and the nickel salt, shape control of the obtained nanowires, and improvement of the yield. The alkaline compound is preferably dissolved in the reaction solvent.

[0024] When sodium hydroxide or potassium hydroxide is added, it reacts with the iron ions and nickel ions generated from each salt, generating a coprecipitate of salts containing iron and nickel. The coprecipitate is difficult to reduce, which causes problems such as a significant delay in the reduction reaction and the generation of scaly or amorphous particles. In the present invention, in order to redissolve the coprecipitate, it is preferable to add ammonia to form an ammine complex. The amount of ammonia added is preferably 3 to 30 mol per mol of the alkaline compound, and from the viewpoints of the reduction reactivity of iron ions and nickel ions, the shape control of the obtained nanowires, and the improvement of the yield, it is preferably 10 to 30 mol, and more preferably 20 to 30 mol. It is preferable to add ammonia water from the viewpoints of handling, etc.

[0025] The reduction reaction is carried out using a reducing agent. Examples of the reducing agent include hydrazine and hydrazine monohydrate. When a reducing agent other than hydrazines, such as a phosphorus-based reducing agent such as hypophosphorous acid or a boron-based reducing agent such as dimethylaminoborane, is used, nanowires may not be obtained.

[0026] When hydrazine monohydrate is used as the reducing agent, the concentration is preferably 1 to 20 mol, more preferably 2 to 10 mol, even more preferably 2 to 4 mol, and particularly preferably 2.5 to 3.5 mol, per mol of the total of the iron salt and nickel salt, from the viewpoints of the reduction reactivity of iron ions and nickel ions, shape control of the obtained nanowires, and improvement of the yield. The order of addition of the nickel salt, iron salt, citrate, ammonia, reducing agent, etc. during the reduction reaction is not particularly limited as long as the reducing agent is added last.

[0027] Nanowires can be obtained by applying a magnetic field during the reduction reaction. The magnetic field can be applied using a magnetic circuit made of a neodymium magnet, and the strength of the magnetic field is preferably about 100 mT, and more preferably 100 to 200 mT.

[0028] The temperature and reaction time of the reduction reaction are not particularly limited as long as the reduction reaction proceeds. For example, when hydrazines such as hydrazine and hydrazine monohydrate are used as the reducing agent, the temperature of the reduction reaction is preferably 70 to 100°C, more preferably 80 to 100°C, and even more preferably 80 to 95°C, from the viewpoints of the reduction reactivity of iron ions and nickel ions, shape control into nanowires, and yield improvement. The reduction time is preferably 30 minutes or more, more preferably 60 minutes or more, from the viewpoints of the reduction reactivity of iron ions and nickel ions, shape control into nanowires, and yield improvement.

[0029] After the reduction reaction, the nanowires can be purified and recovered by filtering or decanting the nanowire dispersion, and preferably by filtering. Examples of the filtering method include suction filtering and pressure filtering.

[0030] The filter used for filtration is not particularly limited as long as it can be used with alkaline solvents or polar solvents. Even if the filter is a hydrophobic filter such as polyvinylidene fluoride resin (PVDF), it can be used if the filtration surface is moistened with alcohol or the like. The pore size of the filter is not particularly limited as long as it is smaller than the length of the nanowires, and specifically, it is preferably 10 μm or less.

[0031] The electromagnetic wave shielding material of the present invention can be obtained by further mixing a dielectric with the purified and recovered nanowires. More specifically, the electromagnetic wave shielding material of the present invention has nanowires dispersed and contained in the dielectric. Examples of the dielectric include compounds other than conductive and semiconductive compounds, such as organic materials such as epoxy resins, acrylic resins, styrene resins, polyester resins, alkyd resins, phenolic resins, urethane resins, polyamide resins, polyimide resins, silicone resins, fluororesins, elastomers, and rubber (particularly natural rubber); and inorganic materials such as ceramics. The dielectric also has an effect as a binder. By mixing the dielectric with the nanowires, it becomes possible to mold them, and an electromagnetic wave shielding material can be obtained. Among these, epoxy resins, silicone resins, fluororesins, and ceramics are preferred because they have excellent heat resistance and low moisture absorption, and epoxy resins and silicone resins are preferred because they have excellent adhesion to electronic components. From the viewpoint of further improving the electromagnetic wave shielding properties (particularly electromagnetic wave absorption properties) of the electromagnetic wave shielding material, the dielectric is preferably a styrene resin, a silicone resin, or an epoxy resin, more preferably a styrene resin or a silicone resin, and even more preferably a styrene resin. The term "resin" is used as a concept including polymers.

[0032] The mass ratio of the nanowires to the dielectric (nanowires / dielectric) in the electromagnetic wave shielding material of the present invention is not particularly limited and is usually 10 / 90 to 95 / 10, and from the viewpoint of further improving the electromagnetic wave shielding property (particularly the electromagnetic wave absorption property), it is preferably 10 / 90 to 90 / 10, more preferably 10 / 90 or more and less than 65 / 35, and further preferably 40 / 60 to 60 / 40. The mass ratio can be appropriately changed depending on whether the electromagnetic wave is shielded by reflection or absorption.

[0033] When the ratio of the nanowires to the total of the nanowires and the dielectric is 10% by mass or more and less than 65% by mass, a dielectric material can be obtained. -2 Ω cm or more (especially 4.4×10 6Such materials can shield electromagnetic waves mainly by absorbing them. Usually, the higher the ratio of nanowires within the allowable range, the higher the performance in terms of electromagnetic wave shielding (particularly electromagnetic wave absorption), but the processability becomes poorer and the processing means may be limited to potting, dipping, screen printing, etc., whereas lowering the ratio of nanowires allows various coatings such as die coater and spray coat, transfer, press molding, etc. From the viewpoint of the balance between electromagnetic wave shielding (particularly electromagnetic wave absorption) and processability, the ratio of nanowires is preferably 40% by mass or more and 60% by mass or less of the total of nanowires and dielectric.

[0034] When the ratio of the nanowires to the total of the nanowires and the dielectric is 65% by mass or more and 90% by mass or less, a conductor can be obtained. -2 The resistivity can be less than Ω·cm. The ratio of the nanowires to the total of the nanowires and the dielectric is more preferably 80% by mass or more and 90% by mass or less. Such materials can shield electromagnetic waves mainly by reflecting them.

[0035] The electromagnetic wave shielding material of the present invention may contain a filler, a softening agent, an antioxidant, a tackifier, etc., within the range that does not impair the effects of the present invention. The electromagnetic wave shielding material of the present invention may be cured (or crosslinked) with a curing agent (or a crosslinking agent).

[0036] The electromagnetic wave shielding material of the present invention can be produced by mixing the iron-nickel nanowires and the dielectric material. The mixing method is not particularly limited, but for example, a method of mixing them in a planetary mixer using a solvent or the like to prepare a dispersion containing the electromagnetic wave shielding material, and molding the dispersion can be used.

[0037] Specifically, for example, when the dielectric is an organic material, the iron-nickel nanowires are dispersed in a solvent containing the organic material to prepare a dispersion, and the dispersion is applied and the solvent is dried to obtain the electromagnetic wave shielding material of the present invention. The organic material may be dissolved or dispersed in the dispersion. A monomer (particularly a polymerizable monomer) capable of forming the organic material may be used as the organic material. In this case, the dispersion may be applied and then polymerized (or cured). In this case, the dispersion may not contain a solvent. The dispersion may also be used as a paste. The above-mentioned dispersion or paste is filled into a plate-shaped template and cured to obtain a sheet.

[0038] Furthermore, for example, when the dielectric material is an organic material, the electromagnetic wave shielding material of the present invention can be obtained by melting and mixing the organic material and the iron-nickel nanowires and molding them.

[0039] Furthermore, for example, when the dielectric material is an inorganic material, the inorganic material and the iron-nickel nanowires can be mixed together with a solvent, and the mixture can be molded and sintered to obtain the electromagnetic wave shielding material of the present invention.

[0040] The present invention also provides a dispersion containing an electromagnetic wave shielding material. A dispersion containing an electromagnetic wave shielding material is a dispersion from which the electromagnetic wave shielding material of the present invention can be produced. The dispersion contains the iron-nickel nanowires constituting the electromagnetic wave shielding material of the present invention, a solvent, and optionally a dielectric (e.g., an organic material or a monomer capable of forming the organic material (particularly a polymerizable monomer)). As the solvent, any solvent used in the field of nanowire dispersions can be used, and examples of the solvent include organic solvents such as toluene, xylene, and methyl ethyl ketone. When a monomer capable of forming the organic material (particularly a polymerizable monomer) is used as the organic material, the dispersion does not need to contain a solvent.

[0041] The shape of the electromagnetic wave shielding material of the present invention is not particularly limited, but may be, for example, a sheet or a film. The electromagnetic wave shielding material of the present invention may also be used as a coating film for various electronic parts such as semiconductors. The sheet and film may have a thickness of 1 μm to 5 mm. The coating film may have a thickness of 1 to 500 μm.

[0042] The electromagnetic wave shielding material of the present invention (particularly the electromagnetic wave shielding material of the present invention in which the ratio of nanowires to the total of nanowires and dielectric is 10% by mass or more and less than 65% by mass) can also absorb electromagnetic waves (electric waves) at frequencies of 18 GHz or more. More specifically, it is preferable that the electromagnetic wave at frequencies of 18 GHz or more has an average absorption of 15 dB or more in any of the following frequency ranges, and furthermore, it is preferable that the electromagnetic wave at frequencies of 18 GHz or more can absorb multiple frequency bands, 3 or more bands, in these ranges. Furthermore, an absorption rate of 15 dB or more is preferable because 97% of the electric wave power can be absorbed, and 20 dB is even more preferable because 99% can be absorbed. (Frequency range) In the fifth generation mobile communication system, n257 (26.50-29.50GHz) used in Japan and South Korea, n258 (24.25-27.50GHz) used in the EU, n259 (39.5-43.50GHz), n260 (37.00-40.00GHz), and n261 (27.50-28.35GHz) used in the United States and China; and Millimeter-wave radar, which is part of advanced driver assistance systems, has the following operating frequencies: 24.05-24.25 GHz for 24 GHz narrowband radar systems, 24.25-29.0 GHz for 24 GHz / 26 GHz UWB radar systems, 60.0-61.0 GHz for 60 GHz millimeter-wave radar systems, 76.0-77.0 GHz for 76 GHz millimeter-wave radar systems, and 77.0-81.0 GHz for 79 GHz high-resolution radar systems.

[0043] The electromagnetic shielding properties of parts using the electromagnetic shielding material of the present invention can be designed to have an absorption rate and shielding rate appropriate for the application. The shielding rate can block 90% of the electromagnetic wave power at 10 dB, 97% at 15 dB, 99% at 20 dB, 99.7% at 25 dB, and 99.9% at 30 dB.

[0044] The electromagnetic wave shielding material of the present invention, by setting the ratio of nanowires to the total of the nanowires and the dielectric material to 40% by mass or more and 60% by mass or less, can exhibit an average absorption of 15 dB or more, particularly 20 dB or more, in the following frequency bands: · n257(26.50-29.50GHz); n261(27.50-28.35GHz); and - 77.0-81.0GHz as a 79GHz band high resolution radar system.

[0045] The electromagnetic wave absorbing property or electromagnetic wave shielding property of the sheet of the present invention can be changed by treating it in a magnetic field. For example, by remelting the electromagnetic wave shielding material of the present invention in a magnetic field and molding it, the absorption rate of a frequency band in which the absorption rate was low can be increased.

[0046] In one embodiment of the present invention, the electromagnetic wave shielding material of the present invention absorbs electromagnetic waves at frequencies of 18 GHz or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 26.5 to 29.5 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 24.5 to 27.5 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 39.5 to 43.5 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 37.0 to 40.0 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 27.5 to 28.35 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 24.05 to 24.25 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 24.25 to 29.0 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 60.0 to 61.0 GHz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having a frequency of 76.0 to 77.0 Hz by an average of 10 dB or more. The electromagnetic wave shielding material of the present invention can absorb electromagnetic waves having frequencies from 77.0 to 81.0 GHz by an average of 10 dB or more.

[0047] In another embodiment of the present invention, the electromagnetic wave shielding material of the present invention, when processed into a sheet having a thickness of 1 mm, can have an average electromagnetic wave absorption property of 10 dB or more at frequencies of 18 to 110 GHz. The electromagnetic wave shielding material of the present invention also has a maximum peak at any frequency of 18 to 110 GHz, and the maximum value of the maximum peak can be 50 dB or more. The electromagnetic wave shielding material of the present invention, when processed into a sheet having a thickness of 1 mm, can further have an average electromagnetic wave shielding property of 10 dB or more at frequencies of 18 to 110 GHz. In the present invention, although the reason is not clear, it is presumed that the specific electromagnetic wave shielding property is exhibited by using nanowires composed of iron and nickel, which have high magnetic permeability.

[0048] In still another embodiment of the present invention, when the electromagnetic wave shielding material of the present invention is used as an electromagnetic wave absorber for noise and the like, the maximum electromagnetic wave absorbency is preferably 20 dB or more, and more preferably 40 dB or more, at a frequency of 18 GHz or more. EXAMPLES

[0049] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0050] The evaluation was carried out by the following methods. A. Evaluation of electromagnetic wave shielding materials (1) Volume resistivity The sheets obtained in the examples and comparative examples were measured at five points in accordance with JIS K 7194 (1994), and the average value was calculated.

[0051] (2) Electromagnetic wave absorption The sheets obtained in the examples and comparative examples were attached with an aluminum plate to serve as samples, and electromagnetic wave absorption measurements were performed on the K band (18-26.5 GHz), Ka band (26.5-40 GHz), U band (40 GHz-60 GHz), E band (60 GHz-90 GHz), and W band (75 GHz-110 GHz) using the free space method with a vector network analyzer. For example, the electromagnetic wave absorption measurement results of the sheet of Example 1 in K band, Ka band, U band, and E band are shown in Figs. 1 to 4, respectively. For example, the electromagnetic wave absorption measurement results of the sheet of Example 5 in K band, Ka band, U band and E band are shown in Figs. 9 to 12, respectively. For example, the electromagnetic wave absorption measurement results of the sheet of Comparative Example 2 in K band, Ka band, U band and E band are shown in Figs. 17 to 20, respectively.

[0052] The measurement results were evaluated by calculating the average absorption rate for each of the following 10 frequency bands: n257 (26.50-29.50GHz), n258 (24.25-27.50GHz), n259 (39.5-43.50GHz), n260 (37.00-40.00GHz), n261 (27.50-28.35GHz), 24GHz narrowband radar system (24.05-24.25GHz), 24GHz / 26GHz UWB radar system (24.25-29.0GHz), 60GHz millimeter wave radar system (60.0-61.0GHz), 76GHz millimeter wave radar system (76.0-77.0GHz), and 79GHz high resolution radar system (77.0-81.0GHz). Each average value was evaluated according to the metal content using the following criteria. In the present invention, the more the range of ◯ or ⊚ is, the more preferable it is in any content.

[0053] For samples containing 50% by mass of metal components, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average absorption rate for each frequency band) ◎: 20dB or more; ○: 15dB or more and less than 20dB; △: 10dB or more and less than 15dB; ×: Less than 10dB. (Overall evaluation of absorption rate for each frequency band) Best: 7 or more ◎ and 〇 frequency bands; Excellent: The number of ◎ and 〇 frequency bands is 6; Good: The number of ◎ and 〇 frequency bands is 5; Acceptable: The number of ◎ and 〇 frequency bands is 3 to 4; Not allowed: The number of ◎ and 〇 frequency bands is 2 or less. In the present invention, when the metal component is contained at 50% by mass, the result of the "overall evaluation of the absorptance in each frequency band" is required to be at a level of "fair" or higher, preferably at a level of "good" or higher, more preferably at a level of "excellent" or higher, and most preferably at a level of "best."

[0054] For the sample containing 20% ​​by mass of a metal component, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average absorption rate for each frequency band) 〇: 10dB or more; ×: Less than 10dB. (Overall evaluation of absorption rate for each frequency band) Excellent: The number of 〇 frequency bands is 3 or more; Good: The number of 〇 frequency bands is 2; Acceptable: The number of frequency bands is 1; Not allowed: The number of ◯ frequency bands is 0. In the present invention, when the metal component is contained at 20% by mass, the result of the "overall evaluation of the absorptance in each frequency band" is required to be at a level of "fair" or higher, preferably at a level of "good" or higher, and more preferably at a level of "excellent."

[0055] For samples containing 10% by mass of metal components, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average absorption rate for each frequency band) 〇: 10dB or more; ×: Less than 10dB. (Overall evaluation of absorption rate for each frequency band) Acceptable: The number of frequency bands marked as ◯ is 1 or more; Not allowed: The number of ◯ frequency bands is 0. In the present invention, when the metal component is contained at 10% by mass, the result of the "overall evaluation of the absorption rate in each frequency band" is required to be at a level of "fair" or higher.

[0056] Next, the average and maximum values ​​and their positions (frequency) of the absorption rate over the entire frequency band from 18 to 110 GHz were determined and evaluated according to the following criteria. (Average absorption rate in the 18-110 GHz band) ◎: 20dB or more; ○: 10 dB or more and less than 20 dB; △: 7.5dB or more and less than 10dB; ×: Less than 7.5dB. In practice, the average value is required to be 7.5 dB or more, preferably 10 dB or more (◯ or ◎), and more preferably 20 dB or more (◎). (Maximum absorption rate from 18 to 110 GHz) ◎: 40dB or more; ○: 20dB or more and less than 40dB; △: 10dB or more and less than 20dB; ×: Less than 10dB. In the present invention, a maximum electromagnetic wave absorbency of 10 dB or more (△) is considered to be acceptable. The maximum electromagnetic wave absorbency is preferably 20 dB or more (◯), and more preferably 40 dB or more (◎).

[0057] (3) Electromagnetic wave shielding property The sheets obtained in the examples and comparative examples were used as samples to perform electromagnetic shielding measurements in K band (18-26.5 GHz), Ka band (26.5-40 GHz), U band (40 GHz-60 GHz), E band (60 GHz-90 GHz), and W band (75 GHz-110 GHz) using the free space method with a vector network analyzer. For example, the electromagnetic wave shielding measurement results for the sheet of Example 1 in K band, Ka band, U band, and E band are shown in Figs. 5 to 8, respectively. For example, the electromagnetic wave shielding measurement results for the sheet of Example 5 in K band, Ka band, U band and E band are shown in Figs. 13 to 16, respectively. For example, the electromagnetic wave shielding measurement results for the sheet of Comparative Example 2 in K band, Ka band, U band and E band are shown in Figs. 21 to 24, respectively.

[0058] To evaluate the measurement results, the average shielding rate for each of the 10 frequency bands, namely n257 (26.50-29.50GHz), n258 (24.25-27.50GHz), n259 (39.5-43.50GHz), n260 (37.00-40.00GHz), n261 (27.50-28.35GHz), 24GHz narrowband radar system (24.05-24.25GHz), 24GHz / 26GHz UWB radar system (24.25-29.0GHz), 60GHz millimeter-wave radar system (60.0-61.0GHz), 76GHz millimeter-wave radar system (76.0-77.0GHz), and 79GHz high-resolution radar system (77.0-81.0GHz), was calculated. Each average value was evaluated according to the content of the metal component according to the following criteria: Note that in the present invention, the more bands marked with ◯ or ⊚, the more preferable it is in any content.

[0059] For samples containing 50% by mass of metal components, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average shielding rate for each frequency band) ◎: 20dB or more; ○: 15dB or more and less than 20dB; △: 10dB or more and less than 15dB; ×: Less than 10dB. (Overall evaluation of shielding rate for each frequency band) Best: 10 frequency bands; Excellent: The number of ◎ frequency bands is 9; Good: The number of ◎ frequency bands is 8; Possible: ◎ Number of frequency bands is 7; Not acceptable: The number of ◎ frequency bands is 6 or less. In the present invention, when the metal component is contained at 50% by mass, the result of the "overall evaluation of the shielding rate for each frequency band" is required to be at a level of "fair" or higher, preferably at a level of "good" or higher, more preferably at a level of "excellent" or higher, and most preferably at a level of "best."

[0060] For the sample containing 20% ​​by mass of a metal component, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average shielding rate for each frequency band) 〇: 10dB or more; ×: Less than 10dB. (Overall evaluation of shielding rate for each frequency band) Excellent: Number of 〇 frequency bands is 9 or more; Good: The number of 〇 frequency bands is 8; Acceptable: The number of frequency bands is 7; Not allowed: The number of ◯ frequency bands is 6 or less. In the present invention, when the metal component is contained at 20% by mass, the result of the "overall evaluation of the shielding rate for each frequency band" is required to be at a level of "fair" or higher, preferably at a level of "good" or higher, and more preferably at a level of "excellent."

[0061] For samples containing 10% by mass of metal components, the average values ​​were evaluated according to the following criteria, and an overall evaluation was also performed. (Average shielding rate for each frequency band) 〇: 10dB or more; ×: Less than 10dB. (Overall evaluation of shielding rate for each frequency band) Best: 5 or more bands with ◯; Excellent: 3 or 4 frequency bands; Good: The number of 〇 frequency bands is 2; Acceptable: The number of frequency bands is 1; Not allowed: The number of ◯ frequency bands is 0. In the present invention, when the metal component is contained at 10 mass %, the result of the "overall evaluation of the shielding rate for each frequency band" is required to be at the level of "fair" or higher.

[0062] Next, the average shielding factor in the 28 GHz band (a 1 GHz-wide frequency band centered on 28 GHz), the average shielding factor in the 79 GHz band (a 1 GHz-wide frequency band centered on 79 GHz), and the average and maximum shielding factors for the entire frequency band from 18 to 110 GHz were calculated and evaluated according to the following criteria. (Average shielding rate for 28GHz, 79GHz and 18~110GHz) ◎:25dB or more; ○: 20dB or more and less than 25dB; △: 10dB or more and less than 20dB; ×: Less than 10dB. In practice, the average value is required to be 10 dB or more, preferably 20 dB or more (◯ or ◎), and more preferably 25 dB or more (◎). (Maximum shielding rate from 18 to 110 GHz) ◎: 70dB or more; ○: 20dB or more and less than 70dB; △: 10dB or more and less than 20dB; ×: Less than 10dB. In the present invention, a maximum electromagnetic wave shielding property of 10 dB or more (△) is considered to be acceptable. The maximum electromagnetic wave shielding property is preferably 20 dB or more (◯), and more preferably 70 dB or more (◎).

[0063] B. Material The nanowires and particles used in the electromagnetic wave shielding material of the present invention were prepared as follows. (1) Nanowire composed of iron and nickel (FeNiNW1, Fe:Ni=21.5:78.5) 15.35 g (64.58 mmol) of nickel chloride hexahydrate and 0.30 g (1.02 mmol) of trisodium citrate dihydrate were added to ethylene glycol to make a total amount of 350.0 g. The solution was heated to 90° C. to dissolve the nickel chloride, and a nickel citrate solution was obtained. 2.50 g (62.52 mmol) of sodium hydroxide was added to the ethylene glycol to make a total amount of 388.5 g. The solution was heated to 90° C. to dissolve the sodium hydroxide, thereby obtaining a sodium hydroxide solution. 3.70 g (18.61 mmol) of iron(II) chloride tetrahydrate was added to ethylene glycol to make a total amount of 150.0 g. The iron(II) chloride tetrahydrate was dissolved by stirring at room temperature to obtain an iron solution. A reaction vessel in a magnetic circuit that can apply a magnetic field to the center was heated to 90-95°C, and 350.0g of nickel citrate solution, 388.5g of sodium hydroxide solution, 100.0g of 28% ammonia water (amount of ammonia: 28.0g), 150.0g of iron solution, and 11.5g (229.72mmol) of hydrazine monohydrate were added in that order. After all of the ingredients were added, a magnetic field of 150mT was applied, and the reduction reaction was carried out at 90-95°C for 90 minutes. After the reaction was completed, the nanowires were collected using a PTFE filter (T100A090C). The recovered nanowires were characterized by ICP-MS, which showed that the iron / nickel mass ratio was 21.5 / 78.5. The average length, diameter, and aspect ratio of the nanowires were 22.6 μm, 0.2 μm, and 113, respectively.

[0064] (2) Nanowires composed of iron and nickel (FeNiNW2, Fe:Ni=55:45) 8.18 g (34.43 mmol) of nickel chloride hexahydrate and 0.30 g (1.02 mmol) of trisodium citrate dihydrate were added to ethylene glycol to make a total amount of 350.0 g. The solution was heated to 90° C. to dissolve the nickel chloride, and a nickel citrate solution was obtained. 2.50 g (62.52 mmol) of sodium hydroxide was added to the ethylene glycol to make a total amount of 388.5 g. The solution was heated to 90° C. to dissolve the sodium hydroxide, thereby obtaining a sodium hydroxide solution. 9.24 g (46.48 mmol) of iron(II) chloride tetrahydrate was added to ethylene glycol to make a total amount of 150.0 g. The iron(II) chloride tetrahydrate was dissolved by stirring at room temperature to obtain an iron solution. A reaction vessel in a magnetic circuit that can apply a magnetic field to the center was heated to 90-95°C, and 350.0g of nickel citrate solution, 388.5g of sodium hydroxide solution, 100.0g of 28% ammonia water (amount of ammonia: 28.0g), 150.0g of iron solution, and 11.5g (229.72mmol) of hydrazine monohydrate were added in that order. After all of the ingredients were added, a magnetic field of 150mT was applied, and the reduction reaction was carried out at 90-95°C for 90 minutes. After the reaction was completed, the nanowires were collected using a PTFE filter (T100A090C). The recovered nanowires were characterized by ICP-MS, revealing that the iron / nickel mass ratio was 54.8 / 45.2. The average length, diameter, and aspect ratio of the nanowires were 24.6 μm, 0.2 μm, and 123, respectively.

[0065] (3) Nanowires composed of iron and nickel (FeNiNW3, Fe:Ni=64:36) 6.89 g (28.99 mmol) of nickel chloride hexahydrate and 0.30 g (1.02 mmol) of trisodium citrate dihydrate were added to ethylene glycol to make a total amount of 350.0 g. The solution was heated to 90° C. to dissolve the nickel chloride, and a nickel citrate solution was obtained. 2.50 g (62.52 mmol) of sodium hydroxide was added to the ethylene glycol to make a total amount of 388.5 g. The solution was heated to 90° C. to dissolve the sodium hydroxide, thereby obtaining a sodium hydroxide solution. 10.78 g (54.17 mmol) of iron(II) chloride tetrahydrate was added to ethylene glycol to make a total amount of 150.0 g. The mixture was stirred at room temperature to dissolve the iron(II) chloride tetrahydrate, and an iron solution was obtained. A reaction vessel in a magnetic circuit that can apply a magnetic field to the center was heated to 90-95°C, and 350.0g of nickel citrate solution, 388.5g of sodium hydroxide solution, 100.0g of 28% ammonia water (amount of ammonia: 28.0g), 150.0g of iron solution, and 11.5g (229.72mmol) of hydrazine monohydrate were added in that order. After all of the ingredients were added, a magnetic field of 150mT was applied, and the reduction reaction was carried out at 90-95°C for 90 minutes. After the reaction was completed, the nanowires were collected using a PTFE filter (T100A090C). The recovered nanowires were characterized by ICP-MS, which showed that the iron / nickel mass ratio was 64.0 / 36.0. The average length, diameter, and aspect ratio of the nanowires were 23.2 μm, 0.2 μm, and 116, respectively.

[0066] (4) Particles composed of iron and nickel (FeNiP) 15.35 g (64.58 mmol) of nickel chloride hexahydrate and 0.30 g (1.02 mmol) of trisodium citrate dihydrate were added to ethylene glycol to make a total amount of 350.0 g. The solution was heated to 90° C. to dissolve the nickel chloride, and a nickel citrate solution was obtained. 2.50 g (62.52 mmol) of sodium hydroxide was added to the ethylene glycol to make a total amount of 388.5 g. The solution was heated to 90° C. to dissolve the sodium hydroxide, thereby obtaining a sodium hydroxide solution. 3.70 g (18.61 mmol) of iron(II) chloride tetrahydrate was added to ethylene glycol to make a total amount of 150.0 g. The iron(II) chloride tetrahydrate was dissolved by stirring at room temperature to obtain an iron solution. The reaction vessel was heated to 90-95°C, and 350.0g of nickel citrate solution, 388.5g of sodium hydroxide solution, 100.0g of 28% ammonia water (amount of ammonia: 28.0g), 150.0g of iron solution, and 11.5g (229.72mmol) of hydrazine monohydrate were added in this order. After all the ingredients were added, the reduction reaction was carried out at 90-95°C for 90 minutes. After the reaction was completed, the nanowires were collected using a PTFE filter (T100A090C). The collected particles were analyzed by ICP-MS, and the mass ratio of iron to nickel was found to be 21.5 / 78.5. Since the particles were in a granular form, the aspect ratio was 1.

[0067] (5) Nickel nanowires (NiNWs) 4.00 g (16.8 mmol) of nickel chloride hexahydrate and 0.375 g (1.27 mmol) of trisodium citrate dihydrate were added to ethylene glycol to make a total amount of 500.0 g. The solution was heated to 90° C. and dissolved to obtain a nickel citrate solution. In a separate container, 1.00 g of sodium hydroxide was added to ethylene glycol to make a total of 499.0 g. The solution was heated to 90° C. and dissolved to obtain a sodium hydroxide solution. A reaction vessel in a magnetic circuit that can apply a magnetic field to the center was heated to 90-95°C, and 500.0 g of nickel citrate solution, 499.0 g of sodium hydroxide solution, and 1.0 g (229.72 mmol) of hydrazine monohydrate were added in that order. After all of the components were added, a magnetic field of 150 mT was applied, and the reduction reaction was carried out at 90-95°C for 90 minutes. After the reaction, the nanowires were collected using a T100A090C PTFE filter. The average length, diameter, and aspect ratio of the nanowires were 24 μm, 0.1 μm, and 240, respectively.

[0068] Example 1 10 g of FeNiNW1, 10 g of styrene resin (St, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 10 g of toluene were mixed in a planetary mixer to obtain a dispersion liquid. The obtained dispersion was cast onto a Teflon sheet, dried at 40° C., and the coating was peeled off from the Teflon sheet to obtain a sheet having a thickness of 1 mm.

[0069] Example 2 10 g of FeNiNW1 and 9 g of TSE3450 (Si, silicone resin manufactured by Momentive Corp.) were mixed in a planetary mixer, and 1 g of TSE3450 (curing agent for silicone resin manufactured by Momentive Corp.) was further mixed therein to obtain a dispersion liquid. The obtained dispersion was cast onto a polycarbonate resin sheet and cured at room temperature for 24 hours or more, and the coating was peeled off from the polycarbonate resin sheet to obtain a sheet having a thickness of 1 mm.

[0070] Examples 3 and 4 A sheet was obtained by carrying out the same operation as in Example 1, except that the mass ratio of the FeNiNW1 to the styrene resin was changed so that the mass ratio of the FeNiNW1 to the styrene resin was the mass ratio in Table 2A or 3A.

[0071] Example 5 Teflon sheets were laminated on both sides of the sheet produced in Example 1 to produce a laminate consisting of Teflon sheet / sheet obtained in Example 1 / Teflon sheet. The thickness of the obtained laminate was fixed at the edge of the laminate with a 1 mm thick spacer plate, and then the laminate was sandwiched between two ferrite magnet plates and heat-treated for 4 hours at 130° C. After that, the laminate was taken out and the Teflon sheet was peeled off to obtain a sheet with a thickness of 1 mm.

[0072] Example 6 13 g of FeNiNW1 and 9 g of jER (Ep, an epoxy resin manufactured by Mitsubishi Chemical Corporation) were mixed in a planetary mixer, and then 4 g of trimethylhexamethylenediamine was added to obtain a dispersion liquid. The obtained dispersion was cast onto a Teflon sheet and cured at 120° C. for 30 minutes or more. The coating was then peeled off from the Teflon sheet to obtain a sheet having a thickness of 1 mm.

[0073] Examples 7 and 8 A sheet having a thickness of 1 mm was obtained by the same procedure as in Example 6, except that FeNiNW1 was changed to FeNiNW2 or FeNiNW3.

[0074] Comparative Example 1 A sheet was obtained in the same manner as in Example 1, except that FeNiNW was changed to FeNiP.

[0075] Comparative Example 2 A sheet was obtained in the same manner as in Example 1, except that FeNiNW was replaced with NiNW.

[0076] Comparative Example 3 A sheet was obtained in the same manner as in Example 2, except that FeNiNW was replaced with NiNW.

[0077] Comparative Example 4 A sheet was obtained in the same manner as in Example 3, except that FeNiNW was replaced with NiNW.

[0078] Comparative Example 5 A sheet was obtained in the same manner as in Example 4, except that FeNiNW was replaced with NiNW.

[0079] Comparative Example 6 A sheet was obtained in the same manner as in Example 1, except that FeNiNW was replaced with AgNW (manufactured by Aldrich).

[0080] The compositions and evaluation results of the electromagnetic wave shielding materials obtained in the examples and comparative examples are shown in Tables 1A, 1B, 1C, 2A, 2B, 2C, 3A, 3B, 3C, 4A, 4B and 4C.

[0081] [Table 1A]

[0082] [Table 1B]

[0083] [Table 1C]

[0084] [Table 2A]

[0085] [Table 2B]

[0086] [Table 2C]

[0087] [Table 3A]

[0088] [Table 3B]

[0089] [Table 3C]

[0090] [Table 4A]

[0091] [Table 4B]

[0092] [Table 4C]

[0093] Examples 1, 2, and 6, which contained 50% metal components, had an electromagnetic wave absorption rate of 15 dB or more in 6 or more of the 10 frequency bands used, and were excellent in terms of electromagnetic wave shielding properties. On the other hand, Comparative Examples 1 to 3 and 6 had the same metal component content as Examples 1, 2, and 6, but did not contain nanowires made of iron and nickel, so the number of bands in which they could absorb 15 dB or more was less than 3 (especially 2 or less), and there were many frequency bands in which they could not adequately absorb, limiting their use as materials.

[0094] Example 3 containing 20% ​​metal components had four frequency bands in which it could absorb 10 dB or more, and was excellent in terms of electromagnetic wave shielding properties as well. In contrast, Comparative Example 4 had no frequency bands in which it could absorb 10 dB or more.

[0095] Example 4 containing 10% metal components had one frequency band in which it could absorb 10 dB or more, whereas Comparative Example 5 had no frequency band in which it could absorb 10 dB or more.

[0096] Example 5 has the same composition as Example 1, but by melting and remolding in a magnetic field, it was possible to confirm a high absorption rate of 20 dB or more for n258 (24.25-27.5 GHz) and a 24 GHz narrowband radar system (24.05-24.25 GHz), which Example 1 was unable to absorb, and for a 24 GHz / 26 GHz UWB radar system (24.25-29.0 GHz), whose absorption rate was less than 15 dB. [Industrial Applicability]

[0097] The electromagnetic wave shielding material of the present invention has excellent electromagnetic wave shielding properties, particularly electromagnetic wave absorption properties, in the high frequency range (particularly the quasi-millimeter wave range and millimeter wave range), and can therefore be suitably used in electronic components for fifth generation mobile communication systems, advanced driving assistance systems, and the like.

Claims

1. An electromagnetic wave shielding material comprising nanowires composed of iron and nickel.

2. 2. The electromagnetic shielding material according to claim 1, wherein the mass ratio of iron to nickel (iron / nickel) in the nanowires is 20 / 80 to 65 / 35.

3. The electromagnetic wave shielding material according to claim 1 or 2, further comprising a dielectric material.

4. 4. The electromagnetic wave shielding material according to claim 3, wherein the dielectric material is a binder.

5. 5. The electromagnetic shielding material according to claim 3, wherein a ratio of the nanowires to a total of the nanowires and the dielectric material is 10% by mass or more and less than 65% by mass.

6. 5. The electromagnetic shielding material according to claim 3, wherein a ratio of the nanowires to a total of the nanowires and the dielectric material is 40% by mass or more and 60% by mass or less.

7. Volume resistivity is 10 -2 7. The electromagnetic wave shielding material according to claim 1, having a resistivity of Ω·cm or more.

8. A dispersion comprising the electromagnetic wave shielding material according to any one of claims 1 to 7.

9. A sheet comprising the electromagnetic wave shielding material according to any one of claims 1 to 7.

10. A film comprising the electromagnetic wave shielding material according to any one of claims 1 to 7.

11. An electronic part comprising the electromagnetic wave shielding material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Nickel nanowire

    JP2017165996A